Technology and livelihood education : a contextualized approach to drafting for k to 12 learners - Laguyo, Cristina B. (Quezon City : St. Bernadette Publishing House Corporation, 2015)
" A contextualized Approach to Drafting for K to 12 Learners is a part of the series of Technology and Livelihood Education where competencies are based on the Department of Education's K to 12 curriculum. This module is divided into five units for the simplification of the topics and for the convenience of both teachers and learners. Each lesson under the different units has Look Back to motivate students, Build Up to further discuss the lesson, Hands On to assess what that students learned, and keep in Mind to summarize the salient points of the lesson. "
Includes bibliography.
English text.
Keywords: Technical drawing; Mechanical drawing